Anionic lipopeptides from Bacillus mojavensis I4 as effective antihypertensive agents: Production, characterization, and identification. Issue 12 (11th September 2017) - Ghazala, Imen; Bouassida, Mouna; Krichen, Fatma; Manuel Benito, José; Ellouz‐Chaabouni, Semia; Haddar, Anissa
Abstract: A new isolated Bacillus mojavensis strain I4 was found as producer of biosurfactants by different screening methods, such as parafilm M test, hemolytic activity, oil displacement test, emulsification index, surface tension, and lipase production assay. Enhanced biosurfactants production was obtained using glucose and glutamic acid as carbon and nitrogen sources, respectively. The optimal production of the biosurfactants was obtained by using a C/N ratio of 17, pH of 7.0, and temperature of 37°C. The surface tension was reduced to 29 mN/m and the emulsification index E24 of 62% was achieved after 72 h of culture. The purified biosurfactants showed stability with regard to surface tension reduction and emulsification in a wide range of temperatures (4–120°C), pH (4–10), and salinity (2–12% of NaCl). The thin‐layer chromatography showed that the produced biosurfactants were lipopeptides. The biosurfactants were characterized as a group of anionic lipopeptides with zeta potential measurement. Chromatographic characterization using HPLC revealed that I4 lipopeptides contained numerous isoforms and surfactin was the major component. Moreover, the I4 lipopeptides showed interesting angiotensin‐converting enzyme‐inhibitory activity.